2015
DOI: 10.1038/srep12538
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Intravenous plus Intraperitoneal Chemotherapy with Intravenous Chemotherapy Alone for the Treatment of Gastric Cancer: A Meta-Analysis

Abstract: We aimed to evaluate the effectiveness and safety of intravenous (IV) plus intraperitoneal (IP) chemotherapy compared to intravenous (IV) chemotherapy alone for patients with gastric cancer. Electronic databases were searched up to June 2013. Two authors independently selected studies, extracted data and assessed the quality of included studies. The GRADE System was adopted to rate the level of evidence. Of 392 citations, five RCTs involving 1072 patients were included. Overall, a significant improvement in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Such dual pathway allows payload delivery to both small avascular nodules and to large vascular tumors. This is an important advantage, as a number of clinical studies on PC indicate that combining systemic and IP chemotherapy results in better outcome than either route alone [58]. …”
Section: Discussionmentioning
confidence: 99%
“…Such dual pathway allows payload delivery to both small avascular nodules and to large vascular tumors. This is an important advantage, as a number of clinical studies on PC indicate that combining systemic and IP chemotherapy results in better outcome than either route alone [58]. …”
Section: Discussionmentioning
confidence: 99%
“…After injection into the peritoneal cavity, a drug or a nanocarrier, is taken up by the surrounding peritoneal tissues, and from there spread into other body compartments via the circulation [66] . Using the IP route not only avoids systemic distribution of the drug, but also provides high concentrations, locally, which are then able to act on the peritoneal tissues directly [67] . Many studies have shown the use of the IP route for cancer therapy including chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic analysis of the distribution of polymersomes in peritoneal and subcutaneous tumors suggested that polymersomes target peritoneal tumors through a combination of direct local penetration and indirect circulation-mediated homing. Such dual targeting is important, as a number of clinical studies indicate that combination of IV and IP chemotherapy for peritoneal carcinomatosis results in better outcome (decreased rate of metastasis, and decreased peritoneal recurrence) than either therapy alone (37). Paclitaxel is very poorly absorbed into the systemic circulation when administered by the IP route, with peak levels in the peritoneal cavity of 1000-fold higher than in the plasma (38), necessitating supplementation of IP paclitaxel with systemic chemotherapies.…”
Section: Discussionmentioning
confidence: 99%